Organic Control Strategies for Use in IPM of Invertebrate Pests in Apple and Pear Orchards - Bethan Shaw; Csaba Nagy; Michelle T. Fountain (Insects, 2021)
Growers of organic tree fruit face challenges in controlling some pests more easily suppressed by broad-spectrum insecticides in conventionally managed orchards. In recent decades, there has been a move towards organically growing varieties normally reliant on synthetic chemical pesticides (e.g., Gala), often to meet retailer/consumer demands. This inevitably makes crop protection in organic orchards more challenging, as modern varieties can be less tolerant to pests. In addition, there have been substantial reductions in plant protection product (PPP) approvals, resulting in fewer chemical options available for integrated pest management (IPM)-maintained orchards. Conversely, the organic management of fruit tree pests involves many practices that could be successfully implemented in conventionally grown crops, but which are currently not. These practices could also be more widely used in IPM-maintained orchards, alleviating the reliance on broad-spectrum PPP. In this review, we evaluate organic practices, with a focus on those that could be incorporated into conventional apple and pear production. The topics cover cultural control, biological control, physical and pest modifications. While the pests discussed mainly affect European species, many of the methods could be used to target other global pests for more environmentally sustainable practices.